2007
DOI: 10.4028/www.scientific.net/kem.353-358.1267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg-Based Spherical Quasicrystals on Microstructure and Mechanical Properties of ZA85 Alloy

Abstract: To improve the strength-toughness and heat-resistance of die cast magnesium alloy, the ZA85 alloy has been prepared by adding proper amount of spherical quasicrystals containing master alloy. The results indicate that the solidification microstructure is inlaid with quasicrystal particles, which is a new phase i(Mg45Zn47Y5Mn3), co-existing with the α-Mg, Φ(Al2Mg5Zn2) phase and τ(Mg32(AlZn)49) phase. Mechanical properties of ZA85 alloys have been dramatically improved owing to the obvious grain refinement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Conventional Casting Process. Zhang et al [14] investigated the microstructure and mechanical properties of ZA85 alloy by adding spherically shaped Mg quasicrystal master alloy into the ZA85 magnesium alloy mother melt at 750 0 C. Typical microstructures of the cast ZA85 alloy with various amounts of the SQCM master alloy are shown in fig. 1.…”
Section: Materials Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional Casting Process. Zhang et al [14] investigated the microstructure and mechanical properties of ZA85 alloy by adding spherically shaped Mg quasicrystal master alloy into the ZA85 magnesium alloy mother melt at 750 0 C. Typical microstructures of the cast ZA85 alloy with various amounts of the SQCM master alloy are shown in fig. 1.…”
Section: Materials Processingmentioning
confidence: 99%
“…Hardness and Impact Toughness. The hardness of ZA85 alloy was extensively studied by Zhang et al [14] who found that the high micro hardness and high melting point of quasicrystal phase improves the macro hardness and strength. Fig.…”
Section: Materials Processingmentioning
confidence: 99%